The emergence of EMERGENCE: the challenge of designing research on the new international division of labour. (1st July 2007) - ,
Abstract : This paper anatomises a pioneering international research project on the global relocation of telemediated employment. It outlines the intellectual origins of the project in the literature on globalisation, the knowledge society, teleworking and other related bodies of work and discusses the limits of the empirical information available up to 2000, when the project was launched. It then summarises the conceptual and methodological framework developed for the project, before discussing some of its limitations, drawing lessons for future international collaborative research on the changing international division of labour.